2022
DOI: 10.3390/cancers14204982
|View full text |Cite
|
Sign up to set email alerts
|

Targeting KRAS in PDAC: A New Way to Cure It?

Abstract: Pancreatic cancer is one of the most intractable malignant tumors worldwide, and is known for its refractory nature and poor prognosis. The fatality rate of pancreatic cancer can reach over 90%. In pancreatic ductal carcinoma (PDAC), the most common subtype of pancreatic cancer, KRAS is the most predominant mutated gene (more than 80%). In recent decades, KRAS proteins have maintained the reputation of being “undruggable” due to their special molecular structures and biological characteristics, making therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 121 publications
0
23
0
Order By: Relevance
“…The results demonstrated that KRAS mutations were prognostically significant in all samples within cluster A (Figure 5A). The KRAS mutation, a key driver gene, leads to the constitutive activation of the RAS/MAPK pathway, which plays a crucial role in cancer initiation, progression and metastasis 25 . Using the hallmark pathway gene set and PI3K/AKT/mTOR entries from the Reactome database, we conducted GSVA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that KRAS mutations were prognostically significant in all samples within cluster A (Figure 5A). The KRAS mutation, a key driver gene, leads to the constitutive activation of the RAS/MAPK pathway, which plays a crucial role in cancer initiation, progression and metastasis 25 . Using the hallmark pathway gene set and PI3K/AKT/mTOR entries from the Reactome database, we conducted GSVA.…”
Section: Resultsmentioning
confidence: 99%
“…The KRAS mutation, a key driver gene, leads to the constitutive activation of the RAS/MAPK pathway, which plays a crucial role in cancer initiation, progression and metastasis. 25 Using the hallmark pathway gene set and PI3K/AKT/mTOR entries from the Reactome database, we conducted GSVA. The heat map revealed significant differences in the top five pathways (Figure 5B), with hypoxia and glycolysis showing high activation in cluster A, while only bile acid metabolism was activated in cluster B.…”
Section: Significant Activation Of Carcinogenic Pathway In Cluster Amentioning
confidence: 99%
“…ctDNA mainly originates from necrotic or apoptotic tumor cells and tumor cell‐secreted extracellular vesicles. Studies have shown that over 90% of PDAC patients have Kirsten rat sarcoma ( KRAS ) gene mutations [19]. Therefore, detecting KRAS mutations in ctDNA holds promise for early diagnosis of PDAC.…”
Section: Making Impossible Early Pdac Screening Possible For Curable ...mentioning
confidence: 99%
“…However, THZ835 had an off-target effect because the inhibition was not fully dependent on KRAS mutation status (Mao et al, 2022). At present, the drug molecules with KRAS G12D protein inhibitory activity reported have made slow progress in research and development (He et al, 2022). The novel molecular skeleton can provide more possibilities for specific effects or clinical studies, so it is necessary to study the new molecular skeleton of KRAS G12D inhibitors (Peng et al, 2018).…”
Section: Figurementioning
confidence: 99%